Efficient platinum harvesting of MOF-derived N-doped carbon through cathodic cyclic voltammetry for hydrogen evolution. (10th September 2019) - Fan, Lili; Du, Xinxin; Zhou, Sainan; Yang, Pu; Li, Mengfei; Kang, Zixi; Guo, Hailing; Fan, Weidong; Kang, Wenpei; Zhang, Ling; Lu, Xiaoqing; Sun, Daofeng
Abstract: Although platinum has been recognized as one of the most efficient catalysts for hydrogen evolution reaction, chemically compatible supports are still needed to address its instability issue. Herein, we demonstrate a rational design and synthesis of a N-doped graphitic carbon material from a N-rich MOF as the superior support for dispersion of platinum. The in-situ doped N atoms play an important role in harvesting and anchoring platinum through the electrochemical process. Compared with carbon nanotubes and graphene oxide, the as-prepared carbon material exhibits exceptional HER performance after platinum decoration with low onset overpotential, small Tafel slope, and high stability in acidic solution. DFT calculations indicate that the superior electrocatalytic activity and high platinum harvesting efficiency is due to the strong interaction between doped N sites and platinum atom, which facilitates the electron transport and hydrogen evolution process. This work would provide some new ideas for designing and fabricating high active and long-time durable HER catalysts with lower platinum loading.